Interactive Affection of Pre-Pregnancy Overweight or Obesity, Excessive Gestational Weight Gain and Glucose Tolerance Test Characteristics on Adverse Pregnancy Outcomes Among Women With Gestational Diabetes Mellitus - Lin, Li-hua; Lin, Juan; Yan, Jian-ying (Frontiers in Endocrinology, 2022)
Purpose: To examine the combined effect of pre-pregnancy overweight or obesity, excessive gestational weight gain, and glucose tolerance status on the incidence of adverse pregnancy outcomes among women with gestational diabetes mellitus. Methods: A observational study including 5529 gestational diabetes mellitus patients was performed. Logistic regression were used to assess the independent and multiplicative interactions of overweight or obese, excessive gestational weight gain, abnormal items of oral glucose tolerance test and adverse pregnancy outcomes. Additive interactions were calculated using an Excel sheet developed by Anderson to calculate relative excess risk. Results: Overall 1076(19.46%) study subject were overweight or obese and 1858(33.60%) women gained weight above recommended. Based on IADPSG criteria, more than one-third women with two, or three abnormal glucose values. Preconception overweight or obesity, above recommended gestational weight gain, and two or more abnormal items of oral glucose tolerance test parameters significantly increased the risk of adverse pregnancy outcomes, separately. After accounting for confounders, each two of overweight or obesity, excessive gestational weight gain, two or more abnormal items of OGTT parameters, the pairwise interactions on adverse pregnancy outcomes appear to be multiplicative. Coexistence of preconception overweight or obesity, above recommended gestational weight gain and two or more abnormal items of oral glucose tolerance test parameters increased the highest risk for adverse pregnancy outcomes. No additive interaction was found. Conclusions: Pre-pregnancy overweight or obesity, excessive gestational weight gain, two or more abnormal items of OGTT parameters contribute to adverse pregnancy outcomes independently among women with gestational diabetes mellitus. Additionally, the combined effect between these three factors and adverse pregnancy outcomes appear to be multiplicative. Interventions focus on maternal overweight or obesity and gestational weight gain should be offered to improve pregnancy outcomes.